Five-year outcomes following a randomized trial of femorofemoral and femoropopliteal bypass grafting with heparin-bonded or standard polytetrafluoroethylene grafts. Issue 10 (1st August 2016) - Lindholt, J S; Houlind, K; Gottschalksen, B; Pedersen, C N; Ravn, H; Viddal, B; Pedersen, G; Rasmussen, M; Wedel, C; Bramsen, M B
Abstract: Background: Cohort studies suggest superior long-term patency of luminal heparin-bonded polytetrafluoroethylene (Hb-PTFE) bypass grafts compared with standard PTFE grafts. The aim of this study was to compare the outcomes of Hb-PTFE grafts with those of standard PTFE grafts 5 years after a randomized trial. Methods: Patients with intermittent claudication or critical limb ischaemia requiring femorofemoral or femoropopliteal bypass grafting were randomized in a clinical trial of Hb-PTFE versus standard PTFE in 11 Scandinavian centres between 2005 and 2009. Patients were followed up for 5 years with clinical assessment and surveillance Duplex ultrasound imaging. The primary endpoint of this study was primary patency. Secondary endpoints included major amputation and mortality. Results: Overall, 569 patients were enrolled in the randomized trial. Some 552 had follow-up data available for analysis of the primary outcome. Use of Hb-PTFE significantly improved patency by 37 per cent at 2 years, but 5 years after randomization there was no difference in primary patency (adjusted hazard ratio (HR) 0·95, 95 per cent c.i. 0·71 to 1·28; P = 0·748). In patients with critical limb ischaemia the use of Hb-PTFE reduced the 5-year risk of loss of primary patency by 37 per cent (HR 0·63, 0·40 to 0·99; P = 0·049). Conclusion: In this study there was no difference in primary graft patency between Hb-PTFE and standard PTFE grafts. Patients receiving Hb-PTFE grafts for critical limb ischaemia were more likely to have a patent graft at 5 years than those with standard PTFE grafts. Abstract : No difference